Beyond Scores: Taiwanese EFL Learners' Perceptions and Experiences with Writing-Integrated Reading Instruction - Maravilla, Wes Harven Guillemer (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
The purpose of this study is to investigate their experiences and attitudes towards various reading strategies following the decrease in EFL students' reading comprehension in Taiwan's senior high schools, as shown in the 2023 Programme for International Student Assessment (PISA) assessment results. Following an explanatory sequential mixed-methods approach, the study favors a qualitative phase that explores students' experiences in the three reading strategies, specifically writing tasks, which facilitate interaction with written texts and foster enhanced learning. The study aims to gain a deeper understanding of how students make sense of and engage with given tasks, including their thoughts, feelings, and subject-related challenges. By investigating these individual perceptions, the research aims to reveal the subtlety of their modes of understanding and pinpoint the elements that favor or inhibit comprehension growth.